2017
DOI: 10.1111/dom.13001
|View full text |Cite
|
Sign up to set email alerts
|

Recent new insights into the role of SNARE and associated proteins in insulin granule exocytosis

Abstract: Initial work on the exocytotic machinery of predocked insulin secretory granules (SGs) in pancreatic β-cells mimicked the SNARE hypothesis work in neurons, which includes SM/SNARE complex and associated priming proteins, fusion clamps and Ca 2+ sensors. However, β-cell SGs, unlike neuronal synaptic vesicles, exhibit a biphasic secretory response that requires additional distinct features in exocytosis including newcomer SGs that undergo minimal docking time at the plasma membrane (PM) before fusion and multi-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 102 publications
(213 reference statements)
0
42
1
Order By: Relevance
“…We took advantage of the βγ-SNAP25 interaction and its ability to serve as a brake on secretion to determine if limiting this physiologic inhibitory pathway could affect insulin secretion and/or weight gain in response to a high fat diet. Though SNAP25 is a well-known component of the insulin exocytosis machinery (13)(14)(15), we observed no alteration in GSIS from SNAP25 Δ3/Δ3 mice. However, adiposity and glucose homeostasis were markedly improved.…”
contrasting
confidence: 80%
See 3 more Smart Citations
“…We took advantage of the βγ-SNAP25 interaction and its ability to serve as a brake on secretion to determine if limiting this physiologic inhibitory pathway could affect insulin secretion and/or weight gain in response to a high fat diet. Though SNAP25 is a well-known component of the insulin exocytosis machinery (13)(14)(15), we observed no alteration in GSIS from SNAP25 Δ3/Δ3 mice. However, adiposity and glucose homeostasis were markedly improved.…”
contrasting
confidence: 80%
“…SNAP25 Δ3/Δ3 mice have marked improvement in glucose homeostasis. Our initial hypothesis was that this would be present because an improvement in insulin secretion as SNAP25 has been show to transduce signals that inhibit insulin secretion (13)(14)(15). In fact, we found that SNAP25 Δ3/Δ3 mice have normal β-cell function and the improvement in glucose homeostasis is because of an improvement in insulin action.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…underlying this timing are believed to be associated with the availability of secretion-ready 65 insulin vesicles that do not depend on changes in Ca 2+ levels (Gaisano, 2017). m 66…”
Section: Introduction 51mentioning
confidence: 99%